Analysis of Trace‐Level Volatile Compounds in Fresh Turf Crop (Lolium perenne L.) by Gas Chromatography Quadrupole Time‐of‐Flight Mass Spectrometry. Issue 10 (16th September 2013) - Hong, Saisai; Kang, Wenyu; Su, Yue; Guo, Yinlong
Abstract In the traditional research of volatile compounds, some trace‐level compounds could not be identified by gas chromatography‐mass spectrometry. Target and post‐targeted methods were applied in the investigation of trace‐level volatile compounds in fresh turf crop (Lolium perenne L.) based on gas chromatography in combination with hybrid quadrupole time‐of‐flight mass spectrometry. According to literatures published, a target analysis was performed by using retention index, accurate masses of characteristic ions and second‐stage mass spectra (MS2 spectra). And a series of experiments showed that low electron impact energy was beneficial to the improvement of the abundances of low abundance molecular ion peak. Enhancing the abundances of low abundance molecular ion peak was beneficial to qualitative analysis. Totally, 60 volatile compounds were identified, the great majority compounds of which were benzeneacetaldehyde (14.8%), 2, 5‐dimethyl‐pyrazine (9.6%), and hexanal (9.3%). Identification was complied by mass spectral search, retention index and accurate masses of characteristic ions.